WADY WRODZONEEarly and late outcome after the arterial switch operation for Taussig-Bing anomaly - Ostrowska, Katarzyna; Moll, Jadwiga; Sysa, Andrzej; Moll, Maciej; Moll, Jacek Jan (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
Background: The arterial switch operation is the preferred choice of corrective technique for simple and complex transposition of the great arteries. The aim of the study was to evaluate the results of the arterial switch operation for Taussig-Bing anomaly. Material and Methods: Between March 1993 and March 2006, 41 patients with Taussig-Bing anomaly underwent the arterial switch operation (ASO) at the Cardiosurgery Department of the Polish Mother’s Memorial Hospital – Research Institute in Lodz. There were 31 boys (75.6%). Pathology of the aortic arch was presented in 23 patients (56%): 7 – CoA, 12 – CoA with hypoplastic arch, 3 – interrupted aortic arch; coronary abnormalities were presented in 18 patients (48.6%). The relationship of arteries was side by side in 15 cases (36.6%). The mean age at the time of operation was 18 days (17.98±14.9). The postoperative evaluation was based on physical examination, ECG, echocardiography and in some cases angiography. Results: There were 6 early deaths and 1 late death. Three patients underwent 8 interventional procedures (5 for right ventricular outlet obstruction – RVOTO, 3 for reCoA). Reoperations were 6 (3 for RVOTO, 1 – reCoA, 1 – LVOTO, 1 – AS). The group with aortic arch pathology has a higher risk of interventions and reoperations. 94% of survivors were New York Heart Association (NYHA) class I, without medication. Aortic regurgitation was noted in 28 patients (82.3%): in most cases trivial or mild, in 2 pts moderate. Conclusions: The arterial switch operation has been accepted as the standard procedure for treatment of Taussig-Bing anomaly. The presence of pathology of the aortic arch or coronary abnormalities or position side by side has no effect on mortality. Anomaly of the aortic arch increases the risk of interventions.